ANALYSIS OF COMPETITIVE ACTIVITY HIGH RANKED FIGHTERS OF MIXED MARTIAL ARTS - Latyshev, Sergii; Latyshev, Mykola; Mavropulo, Olga; Maksimenko, Igor; Tkachenko, Yuri; Zavodnyy, Nikita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Mixed martial arts - a sport, which is a combination of many techniques, schools and direction of combat sports. Nowadays, mixed martial arts are the most popular and spectacular sport of all combat sports. Analysis of competitions performances is an important aspect of training athletes. The quantitative characteristics of competitive activity make it possible to model the training process at different stages of fighters. Aim of the research – to analyze the quantitative characteristics of competitive activity of high ranked fighters. All matches of Mixed martial arts Russian Cup in 2018 were analyzed: 84 preliminary and 8 final fights (for 1 place) in all weight categories. The following quantitative characteristics of the competitive activities of high ranked fighters were analyzed in the study: average fight time; average fight time in the standing and ground positions; distribution of fights by types of victory; activity, defense and reliability performing takedowns for each weight category. Also, a comparative analysis was carried out with the competitive activity characteristics of the top athletes from the Ultimate Fighting Championship rating for each weight group. These data can be used as model when planning the training process of both young and qualified athletes.